Application of The Problem Solving Learning Method in an Effort to Improve The Learning Outcomes of Indonesia Language Procedure Texts of Elementary Students - Rahmadani, Julia; Rahmat Kartolo; Sutikno; Mevy Sitorus, Ruth; Arpah, Juni (PT Inovasi Pratama Internasional, 2026)
This research is motivated by the low learning outcomes of students' procedural texts in the Indonesian Language subject in grade V UPT SD Negeri 060874 Medan City. The learning process is still less active, which causes students to be less enthusiastic in learning. Many students tend to chat or play during lessons, so that the material is not conveyed optimally. This condition has an impact on low student grades in the Indonesian Language subject, especially in understanding and writing procedural texts. Therefore, this study aims to determine whether the application of the Problem Solving method can improve student learning outcomes in learning procedural texts. This study uses a Classroom Action Research (CAR) approach which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects in this study were fifth grade students of UPT SD Negeri 060874 Medan City in the 2025-2026 Academic Year. Data were collected through observation of student activities during learning and learning outcome tests in each cycle to determine the improvements that occurred. The results showed that the application of the Problem Solving method can significantly improve student learning outcomes. In cycle I, the percentage of student learning completion reached 70%, while in cycle II it increased to 95%. Thus, there was an increase of 25% after the application of the Problem Solving method. This increase is also supported by changes in student behavior who are more active in learning, more focused on the material, and able to solve problems given in learning procedural texts. Based on these findings, it can be concluded that the Problem Solving method is an effective learning strategy in improving student learning outcomes. Therefore, this method is recommended to be used in Indonesian language learning to increase student engagement and better learning outcomes